ASSOCIATION OF GENDER WITH DECAYED TOOTH SURFACES - A RECORD BASED STUDY - .N, Shivani; L. , Leelavathi (International Journal of Psychosocial Rehabilitation, 2020)
Aim: Dental caries is one of the most chronic diseases of the oral cavity that interferes with daily activities. The risk of dental caries is increasing in developing countries. It is a multifactorial disease and has become a public health problem. Indices can be used to score decayed surfaces such as DMFS. Hence, this study aims to assess the correlation of gender with decayed tooth surfaces among the patients who were treated at Saveetha Dental College, Chennai. Materials and Methods: A retrospective study, which was executed in the year 2020, examined patient records from June 2019 to April 2020. In this study, 3333 patients for whom the DMFS index was recorded from the Department of Public Health Dentistry, Saveetha Dental College, Chennai, were shortlisted based on the inclusion/exclusion criteria. Data was collected and subjected to statistical analysis. Microsoft excel 2016 (Microsoft office 10) was used to collect data and later was exported to SPSS software (statistical package for social sciences) for Windows 20.0 (SPSS Inc. co, Chicago, USA) and was subjected to statistical analysis and chi-square test was employed with the level of significance set at p<0.05 Results: The prevalence of decayed surfaces was found to be more in males (55.43%) than females (45.57%) Among the age groups of 18-35 years, 36-50 years and 51-70 years, it was more prevalent in 18-35-years-old age group (46.08%) Among the decayed surfaces of groups (1-32 surfaces), (33-64 surfaces), (65-96 surfaces), and (97-128 surfaces), most of the patients had 0-32 decayed surfaces. The correlation between gender and decayed surfaces was found to be insignificant with p> 0.05. Conclusion: Within the limits of the study, the age group of (18-35) years and male patients had a higher prevalence of decayed surfaces than females. However, no significant statistics were found for the prevalence of gender and decayed tooth surfaces (p > 0.05) (chi-square test)